2017
DOI: 10.1021/acs.energyfuels.6b02292
|View full text |Cite
|
Sign up to set email alerts
|

Study of Ionically Modified Water Performance in the Carbonate Reservoir System by Multivariate Data Analysis

Abstract: Adjustment of the ionic composition and strength of injected or imbibed brine for enhanced oil recovery (EOR) in carbonate reservoirs has been an area of active research for the past two decades. Despite many successful laboratory and field applications, the method has been reported ineffective in other cases. Most of the published results attributed EOR to improved water wetness in initially oil-wet carbonates. Nevertheless, in a few studies, EOR was observed without apparent wettability alteration. We undert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 63 publications
0
14
0
Order By: Relevance
“…For limestone core plugs to restore the reservoir wettability, Yi and Sarma suggested that, according to properties of the rock core and fluids, a minimum aging time of three weeks is required [80]: they suggested that a deficiency in aging time may result in improved oil recovery in the secondary oil recovery mode, but limited wettability modification in the tertiary mode. In contrast, it was suggested that aging time and temperature have a negligible impact on oil recovery from chalks, as the oil-rock-brine system reaches equilibrium quickly [111,112]. Pressure may also affect wettability of carbonate rock reservoirs, due to changes in solubility of compounds in the crude oil.…”
Section: Aging Time Temperature and Pressurementioning
confidence: 99%
“…For limestone core plugs to restore the reservoir wettability, Yi and Sarma suggested that, according to properties of the rock core and fluids, a minimum aging time of three weeks is required [80]: they suggested that a deficiency in aging time may result in improved oil recovery in the secondary oil recovery mode, but limited wettability modification in the tertiary mode. In contrast, it was suggested that aging time and temperature have a negligible impact on oil recovery from chalks, as the oil-rock-brine system reaches equilibrium quickly [111,112]. Pressure may also affect wettability of carbonate rock reservoirs, due to changes in solubility of compounds in the crude oil.…”
Section: Aging Time Temperature and Pressurementioning
confidence: 99%
“…12,13 However, these mechanisms are still under debate, especially Karimi et al 13 observed no evidence of SO 4 2− ions adsorbing on the calcite surface using Fourier transform infrared spectroscopy and thermogravimetric analysis, making the surface charge change mechanism questionable. There are also examples showing opposite results against the existing mechanisms; for example, the study of Sohal et al 21 showed that the enhanced oil recovery by smart water flooding is not correlated to the effects of SO 4 2− ions, or the smart waters rich in Ca 2+ ions cannot enhance the water-wettability of carbonate rocks. 22,23 To date, the effects of Ca 2+ , Mg 2+ , and SO 4 2− on carbonate wettability are still not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, numerous studies have shown that the oil recovery from carbonate reservoirs can be significantly enhanced by “smart water” flooding (e.g., 5–25% incremental recoveries). The reason for the enhanced oil recovery can be attributed to an alteration of rock wettability (i.e., from oil-wet to water-wet) under the influences of Ca 2+ , Mg 2+ , and SO 4 2– ions in smart waters. , It was reported that the smart waters containing both SO 4 2– and Ca 2+ (and/or Mg 2+ ) ions are very effective in altering the wettability of calcite surface. Some studies even reported that SO 4 2– or Mg 2+ ion alone can change the wettability of calcite surface, especially at certain pH values, Mg 2+ ion becomes more effective than SO 4 2– in enhancing the water-wetness of calcite surface. The effects of Ca 2+ , Mg 2+ , and SO 4 2– on the wettability alteration of carbonate rocks are complex at molecular perspective, which have been attributed to calcite dissolution, surface charge change, , the combination effect of calcite dissolution and surface charge change mechanisms, or the bridging effect of Mg 2+ and SO 4 2– with the surface complexations of calcium and carboxylic group. , However, these mechanisms are still under debate, especially Karimi et al observed no evidence of SO 4 2– ions adsorbing on the calcite surface using Fourier transform infrared spectroscopy and thermogravimetric analysis, making the surface charge change mechanism questionable. There are also examples showing opposite results against the existing mechanisms; for example, the study of Sohal et al showed that the enhanced oil recovery by smart water flooding is not correlated to the effects of SO 4 2– ions, or the smart waters rich in Ca 2+ ions cannot enhance the water-wettability of carbonate rocks. , To date, the effects of Ca 2+ , Mg 2+ , and SO 4 2– on carbonate wettability are still not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…The performance of smart water flooding is closely related to the ionic chemistry of smart waters. In recent years, many studies showed that the oil recovery of carbonate rocks had been improved by sulfate-rich seawaters when the sulfate concentration (denoted [SO 4 2– ]) in seawater was increased to 2–4 times (up to 0.072 M), whereas the oil recovery started to decrease beyond the limit of 4 times (or 4 × [SO 4 2– ]). , Interestingly, the statistical analysis by Sohal et al suggested that this improvement in oil recovery was not correlated to [SO 4 2– ] but to magnesium concentration (denoted [Mg 2+ ]) in smart waters, although the exact roles of Mg 2+ ions in carbonate recovery are still under debate. The studies by Austad’s group suggested that Mg 2+ ions shall be used with SO 4 2– ions and especially at high temperatures (>90 °C) to enhance the oil recovery of carbonate rocks.…”
Section: Introductionmentioning
confidence: 99%
“…2− ]). 16,17 Interestingly, the statistical analysis by Sohal et al suggested that this improvement in oil recovery was not correlated to [SO 4 2− ] but to magnesium concentration (denoted [Mg 2+ ]) in smart waters, 18 although the exact roles of Mg 2+ ions in carbonate recovery are still under debate. The studies by Austad's group suggested that Mg 2+ ions shall be used with SO 4 2− ions and especially at high temperatures (>90 °C) to enhance the oil recovery of carbonate rocks.…”
Section: Introductionmentioning
confidence: 99%